Nutrition considerations in special environments for aquatic sports - Stellingwerff, T.; Pyne, D. B.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Elite athletes who compete in aquatic sports face the constant challenge of arduous training and competition schedules in difficult and changing environmental conditions. The huge range of water temperatures to which swimmers and other aquatic athletes are often exposed (16-31 °C for open-water swimming), coupled with altered aquatic thermoregulatory responses as compared with terrestrial athletes, can challenge the health, safety, and performance of these athletes. Other environmental concerns include air and water pollution, altitude, and jetlag and travel fatigue. However, these challenging environments provide the potential for sev- eral nutritional interventions that can mitigate the negative effects and enhance adaptation and performance. These interventions include providing adequate hydration and carbohydrate and iron intake while at altitude; optimizing body composition and fluid and carbohydrate intake when training or competing in varying water temperatures; and maximizing fluid and food hygiene when traveling. There is also emerging information on nutritional interventions to manage jetlag and travel fatigue, such as the timing of food intake and the strategic use of caffeine or melatonin. Aquatic athletes often undertake their major global competitions where accom- modations feature cafeteria-style buffet eating. These environments can often lead to inappropriate choices in the type and quantity of food intake, which is of particular concern to divers and synchronized swimmers who compete in physique-specific sports, as well as swimmers who have a vastly reduced energy expenditure during their taper. Taken together, planned nutrition and hydration interventions can have a favorable impact on aquatic athletes facing varying environmental challenges.